Pemanfaatan Teknologi Informasi Dalam Peningkatan Penjualan Pada Perusahaan Percetakan Excellent Di Surabaya - Deograsias Yoseph Yustinianus Ferdinand; Jeanne Asteria Wawolangi (Universitas Katolik Darma Cendika, 2020)
The development of information systems especially in the technological aspects is a challenge and an opportunity for Excellent printing companies. These challenges and opportunities as a stimulation to improve the quality and quantity of sales of printed products such as form of brochures, banners, invitations card, notes, and others. In this case the leadership of the company must be aware that the contribution of systems and information technology can provide maximum benefits for the continuance of the company. Information systems and technology can support the process of selling activities more effectively and optimally, so that company revenue can increase. There needs to be real communication, especially with potential customers so that the sales process can run fluently and continuously, but it must be followed by product innovation.